A revista íntima como cláusula restritiva de direitos fundamentais no direito do trabalho - Nunes, Rosana Marques (2008)
The objective of this study is to demonstrate, through doctrinaire and jurisprudential researches, which the practice of reviewing the employees, commonly made by employers, can invade the sphere of privacy of the employee injuring his dignity. Certainly, in relation to employment there is, on the one hand, a legal subordination of the employee and on the other, the power of direction of the employer, and that with this plea power of direction and the right of property, the employer use the review as a way of protecting his heritage. The practice of review is considered restrictive clause of fundamental rights, and, therefore, there are obvious limits to the actions of the employer in this regard. The magazine is divided into personal or intimate reviews and revised in personal objects, being the first performed on the body of the employee, and the second made in pockets, bags and in the employees vehicles. We defend, in the present study, that the intimate reviews are prohibited by injuring the dignity of the human being, while the reviews in the employee's personal objects can be charged, but respecting some rules. To reach such conclusions our study examined the work freedom, the relation of work and legal subordination, the power of direction, its tracks and limits, the right of ownership, the fundamental rights, human dignity, constitutional principles applied to the work relations, the protection of privacy, the collision of principles and horizontal effectiveness of fundamental rights. We also analised the position adopted by the Law compared and the positioning of the International Labor Organization concerning the issue, in addition to mechanisms adopted by the Labor Law as a way of repairing the damage caused to employees and the role of Labor Public Ministry and the unions related to the practice of reviewing